Pelatihan dan Sosialisasi Financial Teknologi terhadap Bahaya Penyalahgunaan Informasi Transaksi Elektronik (ITE) di Lingkungan Benda Baru Pamulang - Edi Sofwan; Muhamad Eko Ariwibowo; Mohamad Safi”I; Muhammad Sopiyana; Nuriana Nuriana (Abdimisi, 2020)
Based on observations, there are locations where the community has advanced in the level of using financial technology, including those located not far from Pamulang University. However, this knowledge of financial technology must also be equipped with knowledge about the dangers of misuse of technology and information, especially in social media and also crimes in financial technology. This Community Service is carried out using the Training method, mentoring socialization which is carried out with the aim of brainstorming to open a mindset about the importance of using financial technology (fintech) and being aware of the dangers and understanding of the ITE Law, Law no. 11 of 2008 concerning Transaction and Electronic Information. The result of this Community Service is that participants become more aware of the use of financial technology (fintech) so that they feel safe in transactions. The community is increasingly facilitated and facilitated by increasingly understanding the conveniences obtained from the fintech. With this Community Service, people who follow and absorb the material presented can keep up with the times that are increasing rapidly in a safe and advanced manner.